Muscle co-activity tuning in Parkinsonian hand movement: disease-specific changes at behavioral and cerebral level - van der Stouwe, A. M. M.; Toxopeus, C.M.; de Jong, B.M.; Yavuz, P.; Valsan, G.; Conway, B.A.; Leenders, K.L.; Maurits, Natasha M. (Frontiers in Human Neuroscience, 2015)
We investigated different degrees of muscle co-activity in simple hand movement at behavioral and cerebral level in healthy subjects and Parkinson’s disease (PD) patients. We compared ‘singular’ movements, dominated by the activity of one agonist muscle, to ‘composite’ movements, requiring conjoint activity of multiple muscles, in a center-out (right hand) step-tracking task. Behavioral parameters were obtained by EMG and kinematic recordings. FMRI was used to investigate differences in underlying brain activ¬¬ations between PD patients (N= 12) and healthy (age-matched) subjects (N= 18). In healthy subjects, composite movements recruited the striatum and cortical areas comprising bilaterally the supplementary motor area and premotor cortex, contralateral medial prefrontal cortex, primary motor cortex, primary visual cortex, and ipsilateral superior parietal cortex. Contrarily, the ipsilateral cerebellum was more involved in singular movements. This striking dichotomy between striatal and cortical recruitment versus cerebellar involvement may reflect the complementary roles of these areas in motor control, in which the basal ganglia are involved in movement selection and the cerebellum in movement optimization. Compared to healthy subjects, PD patients showed decreased activation of the striatum and cortical areas in composite movement, while performing worse at behavioral level. This implies that PD patients are especially impaired on tasks requiring highly tuned muscle co-activity. Singular movement, on the other hand, was characterized by a combination of increased activation of the ipsilateral parietal cortex and left cerebellum. As singular movement performance was only slightly compromised, we interpret this as a reflection of increased visuospatial processing, possibly as a compensational mechanism.